Os elos e as contradições entre a normatização do patrimônio e o espaço vivido no bairro Padre Faria em Ouro Preto (MG) - Paula Lara Leite da Silva (2021)
The patrimonialization of Brazilian colonial cities is part of a historical process that involves the architecture that was intended to be valued against the action of time in given spaces. Considering this, this master's research aimed to analyze Padre Faria, a neighborhood in the city of Ouro Preto (MG), periphery of the main protection area, located at the end of the path of the Caminho Tronco, in view of the transformations resulting from the constant urban processes inherent to an inhabited city. The choice of the neighborhood was due to the alterity that currently characterizes it, when compared to the institutionalized image of the city of Ouro Preto, given the homogenization of the heritage logic. With this in mind, in the first moment of the research, the spatial and temporal contextualization of the neighborhood was elaborated, based on a bibliographic review, demonstrating its role in the city's formation scenario, as well as its subsequent development. In the second moment, the actual configuration of the neighborhood was analyzed, in direct relation with the central nucleus and with the logic of the colonial imposed on the city, through in loco research. Finally, the residents of Padre Faria were interviewed, considering that they are the main responsible for the specific features of the neighborhood, through their properties, their daily practices and appropriations of public space. From the understanding of the territory of Ouro Preto, with its various layers superimposed over the years, it is necessary to draw up preservation guidelines that are more consistent with the urban core and, especially, with its resident population in view of its everyday logic.